Influence of health-normalizing walking regimens on the state of the respiratory system of students with chronic bronchitis - Oleksandr Petruhnov (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to determine the influence of the types of walking on the state of the respiratory system of students with chronic bronchitis in the period of convalescence. Material & Methods: 73 students were studied at the age of 17-20 years, MG1 (n=25) and MG2 (n=21) were engaged in the developed program, but MG1 students additionally applied the types of walking and running at various health-normalizing regimes, CG (n=27) did not have bronchopulmonary pathology and were engaged in physical culture according to the program of the university. All students underwent spirometric studies, hypoxic tests. Results: at the end of the course of physical rehabilitation of students of MG1, spirometric indicators were statistically significantly improved and reached the level of CG indices. MG2 students observed improvement in all parameters, but they did not receive any statistical significance. Conclusion: it is proved that the inclusion in the program of physical rehabilitation during the convalescence period of varieties of walking and running on various health-normalizing regimes promotes the complete restoration of the lost functions of the respiratory system.